Molecules and morphology reveal a new aberrant harvestman genus of Ortholasmatinae (Opiliones, Dypsnoi, Nemastomatidae) from Mexico. Issue 7 (3rd October 2018) - Cruz-López, Jesús A.; Cruz-Bonilla, Akeri; Francke, Oscar F.
Abstract : Ortholasmatinae is one of the most striking groups of Opiliones, because its members exhibit a peculiar dorsal ornamentation pattern of cells, formed by fusion of anvil-shaped tubercles. During the systematic revision of several specimens of ortholasmatines, we found specimens with shared morphological characters with two genera Trilasma Goodnight & Goodnight, 1942 and Dendrolasma Banks, 1894. In order to investigate their phylogenetic relationships, we performed model-based phylogenetic analyses using the mitochondrial protein-encoding cytochrome c oxidase subunit 1 (CO1) and the complete nuclear ribosomal small subunit 18S, including members of the five genera of this subfamily. The results support the creation of Cryptolasma Cruz-López, Cruz-Bonilla & Francke, gen. nov., and two new species: Cryptolasma aberrante Cruz-López, Cruz-Bonilla & Francke, sp. nov. (type species) and Cryptolasma citlaltepetl Cruz-López, Cruz-Bonilla & Francke, sp. nov., which are from Xalapa and Orizaba Volcano, Veracruz, respectively. Additionally, our results suggest Ruaxphilos petrukenvitchou Goodnight & Goodnight, 1945 is a nomina dubia . This study represents the first molecular hypothesis of Ortholasmatinae relationships, with Cryptolasma as the sister of the remaining ortholasmatine.www.zoobank.org/urn:lsid:zoobank.org:pub:3730EE48-9802-4B06-9DDF-EC1AFE9A3B61